Mother’s Knowledge in Providing Nutrition for Children in The Working Area of East Denpasar I Primary Health Care Centre - Puspita, Luh Mira; K, Francisca Shanti; Karin, Putu Ayu Emmy Savitri (Journal of A Sustainable Global South, 2022)
The nutritional problem in young children particularly nutrition deficiency and over nutrition are still exist. Nutritional intake is one of the most outstanding factors in determining children’s nutritional status. Providing adequate nutrition for children is influenced by their mothers’ knowledge. Hence, by giving health education to mothers was expected to increase mothers’ knowledge in providing adequate nutrition for their children. Regarding this, the information was delivered to mothers by using booklet as the health education media.  The aim of present study was to analyze the influence of health education towards the mothers’ knowledge in providing nutrition for their children. This study was a pre experimental study with one group pretest-posttest design. The population of the present study were mothers who have children aged under five years old and living in working area of East Denpasar I primary health care center. In order to decide the location (banjar) of the study, the simple random sampling was used. Meanwhile, the total sampling was used to recruit the mothers in the selected location. The Wilcoxon Test was performed since the data not normally distributed (? = 0.05, CI = 95%). Finding showed that there was a significant difference in mothers’ knowledge before and after given health education about providing nutrition for their children.